Teori Kriminologi dalam Mengkaji Faktor Penyebab Perilaku Konsumsi Minuman Beralkohol dan Implikasinya sebagai Pemicu Tindak Kriminal yang Ditoleransi dalam Masyarakat - Dwight Nusawakan; Abdul Malik Mufty (Badan Penerbit STIEPARI Press, 2025)
The negative phenomenon often encountered in society is that consuming alcoholic beverages, commonly known as hard liquor, has become an inseparable part of daily life. Many crimes can occur as a result of consuming alcoholic beverages, such as assault, domestic violence, murder, sexual violence, even leading to death. Alcoholic beverages are often one of the driving factors influencing someone to commit such acts. The approach method used in this paper is normative juridical research (normative legal research method). Normative juridical research is a library-based legal study conducted by examining secondary materials or data. The consumption of alcoholic beverages and accompanying criminal acts are influenced by social interactions, cultural norms, and societal control, making criminological theory approaches essential for comprehensively understanding this phenomenon. Preventive solutions must be holistic, incorporating educational and rehabilitative approaches, as well as active roles from the government and society, to create a healthier and more law-aware social environment. In addition, it is important to analyze the role of legislation in regulating the circulation and consumption of alcoholic beverages. Although some legal instruments already exist, enforcement remains weak, allowing easy access to alcohol in many regions. This situation is worsened by the lack of public awareness about the dangers of alcohol consumption and the social tolerance that still exists in some communities. Educational institutions, religious leaders, and community organizations need to be actively involved in preventive measures by instilling moral values, providing counseling, and creating alternative activities that engage youth positively. Rehabilitation programs should also be strengthened to assist individuals who are already dependent on alcohol, offering them medical, psychological, and social support to recover and reintegrate into society. Furthermore, international perspectives show that countries with strict regulations and strong community engagement tend to succeed in reducing alcohol-related crimes.